The Effectifeness of Religious Image Stories Teaching Materials on the Learning achievement of Students' Class 1 SD Negeri 31 Pusuea - Marliana, Marliana (USN Kolaka, 2022)
This study aimed to determine the effectiveness of religiously charged pictorial story teaching materials on learning achievement. The subject of this research was the 1st-grade students of SD Neg. 31 Pusuea with a total of 14 students. The teaching material used is a picture book containing religious values. This study used experimental research methods with the research design used as pre-experiment one group pre-test-posttest. The test questions were in the form of multiple choices with a total of 20 questions. Data analysis used Normalized Gain Test. The results showed that the total pretest score of all students was 1890 and the total post-test score of all students was 2480. These results were processed using the N-Gain formula and reached a value of 0.53 with the interpretation of